The Effect of Canva-aided Problem Based Physics Learning toward Students’ Conceptual Understanding of Static Fluid: A Case of SMAN 7 Bengkulu - Anggraini, Jessica Artsheila; Purwanto, Andik; Setiawan, Iwan (FKIP Universitas Lampung, 2023)
Abstract: This research was conducted with the aim of seeing and describing the influence of the Canva-assisted Problem Based Learning Model on Understanding Physics Learning Concepts at SMAN 7 Bengkulu City. The sampling technique in this research was purposive sampling and class XI IPA 3 was chosen as the experimental class and class XI IPA 5 as the control class. The design in this research is Nonequivalent Control Groups Design. The research instrument used was a concept understanding test. The results obtained in this research indicate the influence of the Canva-assisted Problem Based Learning Model on Understanding Physics Learning Concepts at SMAN 7 Bengkulu City. The hypothesis test used in this research is the Mann Whitney Test on the basis of decision making if the Asymp value. Sig (2-tailed) < 0.05 then the hypothesis is accepted. The magnitude of the influence of the problem based learning model assisted by Canva on the understanding of physics learning concepts at SMAN 7 Bengkulu City, calculated by calculating the effect size, obtained an influence of 3.12, meaning that the influence given is very high. Keywords: understanding concepts, problem based learning, effect size. Abstrak: Penelitian ini dilakukan bertujuan untuk melihat dan mendeskripsikan Pengaruh Model Problem Based Learning Berbantuan Canva Terhadap Pemahaman Konsep Belajar Fisika Di SMAN 7 Kota Bengkulu. Teknik pengambilan sampel dalam penelitian ini adalah purposive sampling dan terpilihlah kelas XI IPA 3 sebagai kelas eksperimen dan kelas XI IPA 5 sebagai kelas kontrol. Desain dalam penelitian ini adalah Nonequivalent Control Groups Design. Instrumen penelitian yang digunakan adalah berupa tes pemahaman konsep. Hasil yang didapatkan pada penelitian ini menunjukkan adanya pengaruh Model Problem Based Learning Berbantuan Canva Terhadap Pemahaman Konsep Belajar Fisika Di SMAN 7 Kota Bengkulu. Uji hipotesis yang digunakan dalam penelitian ini adalah Uji Mann Whitney dengan dasar pengambilan keputusan jika nilai Asymp. Sig (2-tailed) < 0,05 maka hipotesis diterima. Besar Pengaruh Model Problem Based Learning Berbantuan Canva Terhadap Pemahamn Konsep Belajar Fisika Di SMAN 7 Kota Bengkulu yang dihitung dengan rumus Effect Size didapatkan pengaruh sebesar 3,12, artinya pengaruh yang diberikan sangat tinggi. Kata kunci: pemahaman konsep, problem based learning, effect size. DOI: http://dx.doi.org/10.23960/jpmipa/v24i4.pp867-879